Treatment of petroleum hydrocarbon-polluted groundwater with innovative in situ sulfate-releasing biobarrier. (1st May 2021) - Hsia, K.F.; Chen, C.C.; Ou, J.H.; Lo, K.H.; Sheu, Y.T.; Kao, C.M.
Abstract: Petroleum hydrocarbons are commonly found pollutants in groundwater at industrial and gas station sites. Enhanced bioremediation is a cost-effective approach to cleanup petroleum hydrocarbon-polluted groundwater. The applicability of using sulfate-reducing biobarrier on the containment and control of petroleum-hydrocarbon plumes were assessed by batch and column studies. The innovative in situ biobarrier contained sulfate-releasing materials (SRMs) for a long-term sulfate release to enhance anaerobic petroleum hydrocarbons biodegradation with sulfate reduction mechanisms. SRMs were developed by blending rice husk powder (or starch) (used as permeability increment materials), magnesium sulfate (used as a source of sulfate), and polylactic acid (PLA) (used as a binder) together using a kneader. The mixed components were smelted to form pasty liquid at 190 °C, and it was transferred to a cylinder container to form SRMs. A column study was used to investigate the effectiveness of developed SRMs on the treatment of a methyl tert-butyl ether (MTBE) and toluene contaminated groundwater. The optimal sulfate release rate was achieved when the mass ratio of sulfate/starch/PLA was 0.5/0.5/2 [sulfate release rate (mg.d −1 .g −1 ) = −0.009 × release period (d) + 3.4 (mg). Approximately 70% of MTBE and 92% of toluene could be remediated via sulfate reduction processes because the released sulfate from SRMs were served as electron acceptors, which promoted the growth of sulfate reducers. The next generation sequencing data suggest that bacterial strains with sulfate reduction and petroleum hydrocarbon biodegradation functions were detected after SRM supplement. Evidences of sulfate reduction of toluene and MTBE included (1) increased concentrations of sulfate and sulfide, (2) decreased concentrations of toluene and MTBE, (3) production of tert-butyl alcohol (degradation byproduct of MTBE), and (4) increased sulfate-reducing and petroleum-hydrocarbon bacteria. The biobarrier system containing the SRMs can be developed into a pragmatic technology for in situ remediation of petroleum-hydrocarbon plumes. Graphical abstract: The innovative in situ biobarrier contains sulfate-releasing materials (SRMs), which can be used for a long-term sulfate release to enhance the anaerobic biodegradation of petroleum hydrocarbons. Image 1 Highlights: Sulfate-reducing barrier was developed to in situ bioremediate polluted groundwater. Sulfate-releasing materials (SRMs) could release sulfate continuously and passively. SRMs contained magnesium sulfate, starch, and PLA (mass ratio = 0.5/0.5/2). SRM barrier could control toluene and MTBE plume under sulfate-reducing mechanisms.